Syringomatous Tumor of the Breast: A Case Report - Noles, Juliane Maria Mota; Santos, Luana Kauany de Sá; Novaes, Ana Flávia; Laguna, Gabriela Garcia de Carvalho; Figueiredo, Priscilla Teixeira; Ferraz, Monalisa Ferraz de (Brazilian Journal of Case Reports, 2026)
Syringomatous tumor is a rare and benign clinical condition, first described in 1983, characterized by infiltrative glandular proliferation that can affect the nipple-areola complex. Due to its rarity and clinical presentation, the differential diagnosis with malignant neoplasms represents a challenge. In this report, through the collection and analysis of medical records, we present the case of a 29-year-old female patient with a history of a persistent eczematous lesion on the left nipple, accompanied by nipple discharge. After several clinical and radiological evaluations, including ultrasounds and biopsies, surgical excision of the lesion was performed and histopathological analysis revealed a syringomatous tumor, with compromised surgical margins, but no evidence of malignancy. The patient was initially treated with local resection, but developed postoperative necrosis, requiring additional interventions. Despite being a benign lesion, local recurrence is a risk when excision is not complete. The present case emphasizes the importance of an accurate diagnosis and an appropriate therapeutic approach to prevent recurrences and unnecessary surgical complications. Keywords: Breast Neoplasms; Breast Tumor; Case Report; Diagnosis Differential; Syringomatous tumor.